2007
DOI: 10.1080/03602530600952172
|View full text |Cite
|
Sign up to set email alerts
|

What is the Objective of the Mass Balance Study? A Retrospective Analysis of Data in Animal and Human Excretion Studies Employing Radiolabeled Drugs

Abstract: Mass balance excretion studies in laboratory animals and humans using radiolabeled compounds represent a standard part of the development process for new drugs. From these studies, the total fate of drug-related material is obtained: mass balance, routes of excretion, and, with additional analyses, metabolic pathways. However, rarely does the mass balance in radiolabeled excretion studies truly achieve 100% recovery. Many definitions of cutoff criteria for mass balance that identify acceptable versus unaccepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 128 publications
13
152
1
2
Order By: Relevance
“…Studies in rat and dog models have indicated good mass balance and no tissue accumulation of radioactivity (data not shown). The problems sometimes associated with attaining complete mass balance in human absorption, distribution, metabolism, and elimination studies have been documented in a recent review of the subject (Roffey et al, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Studies in rat and dog models have indicated good mass balance and no tissue accumulation of radioactivity (data not shown). The problems sometimes associated with attaining complete mass balance in human absorption, distribution, metabolism, and elimination studies have been documented in a recent review of the subject (Roffey et al, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Quantitative radiometric profiling of metabolites in biological fluids from these studies can be difficult because the drug-related material becomes too dilute. Also, it has been shown that recovery of radioactivity in an excretion study is lower when the half-life of the compound is long (1).…”
Section: Introductionmentioning
confidence: 99%
“…There may be many causes of incomplete recovery of the radiolabel in mass balance trials (such as technical limitations and tissue retention), and it is actually rare for the mass balance in radiolabeled excretion studies to truly achieve 100% recovery [16]. 16 The minimal role of metabolism in the clearance of sugammadex is fully in line with the excretion profile of other cyclodextrins, which has been noted to be almost entirely renal [14,15,17,18], particularly in man. Subsequent profiling for metabolites in urine and plasma samples demonstrated that the major part of total radioactivity could be attributed to the parent compound, sugammadex (data on file).…”
Section: Safety and Tolerabilitymentioning
confidence: 79%
“…There may be many causes of incomplete recovery of the radiolabel in mass balance trials (such as technical limitations and tissue retention), and it is actually rare for the mass balance in radiolabeled excretion studies to truly achieve 100% recovery [16]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Studies in volunteers and surgical patients receiving sugammadex to reverse rocuronium-or vecuronium-induced blockade have also demonstrated that the predominant route of elimination for the complex is via the renal route, and in the presence of sugammadex, the major route of elimination of rocuronium changes from the hepatic to the renal route [10][11][12].…”
Section: Enrollment and Subject Baseline Characteristicsmentioning
confidence: 99%